Peningkatan Pengetahuan Mengenai Cara Latihan Terapi Fisik Sederhana di Rumah pada Penderita Pasca Stroke di Poliklinik RSUD Lombok Barat - Harahap, Herpan Syafii; Susilawati, N Nyoman Ayu; Prafica, Adisti; Setianto, Catur Ari; Mayza, Adre (Universitas Mataram, 2024)
Stroke is a focal or global clinical sign that occurs suddenly disrupts cerebral function, lasting more than 24 hours or causes death for no other reason than vascular. Stroke is the second leading cause of death and dementia and long-term disability worldwide. Approximately 85% of strokes are ischemic and 15% of strokes are intracerebral hemorrhage. Post-stroke disability can worsen the patient’s quality of life due to difficulty carrying out daily activities. Spontaneous recovery of maximum function after stroke occurs within 3 months. Neurorehabilitation with specific exercise techniques (task specificity) triggers disability improvement by activating neuroplasticity mechanisms. Post-stroke patients are limited in carrying out rehabilitation therapy in developing countries because there are various obstacles such as high transportation costs to health facilities and the need for family assistance while undergoing therapy, so one effort to overcome this problem is by providing training in basic rehabilitation techniques that can be carried out by the patient and family themselves at home to achieve optimal recovery of disability in post-stroke patients. This program’s activity used the PowerPoint and liquid crystal display media matriculation method, attended by 16 family participants and post-stroke patients at the West Lombok Regional Hospital's Neurology Clinic. Data analysis on changes in participants' pre-test and post-test knowledge showed that there was a significant increase in participants' knowledge regarding stroke and neurorehabilitation therapy exercise techniques with p<0.05. This result shows that this program’s activity can increase participants' knowledge about stroke and neurorehabilitation therapy exercise techniques at home.